Ngurit: Ritual Awal dalam Tradisi Pertanian Bali untuk Menghormati Bumi dan Kehidupan: Ritual Awal dalam Tradisi Pertanian Bali untuk Menghormati Bumi dan Kehidupan - Gaduh, Acyutananda Wayan; Widyawati, Anak Agung Ayu Alit (Sphatika: Jurnal Teologi, 2024)
Traditional Balinese agricultural practices are rooted in the life philosophy of the Hindu community, which emphasizes harmony between humans, nature, and spirituality, aligning with the Tri Hita Karana philosophy. The Subak, Bali's traditional agricultural organization, manages a farming system rich with agricultural rituals. Among these is the Ngurit ritual, a crucial part of the rice cultivation cycle, performed before the planting season to seek blessings from Dewi Śrī and Dewi Pṛthvī for a bountiful crop. Beyond tradition, Ngurit symbolizes respect for nature as a source of life. Amid modernization and global challenges such as climate change and shifts in younger generations' focus, traditional farming practices face significant pressures threatening their continuity. Through a holistic and regenerative approach, Ngurit also offers valuable perspectives on environmental conservation and sustainable agriculture. This article highlights the need to preserve the spiritual and ecological values embedded in traditional Balinese farming practices to ensure the well-being of Bali’s environment and the lives of future generations.